2015
DOI: 10.3745/jips.04.0013
|View full text |Cite
|
Sign up to set email alerts
|

Prediction & Assessment of Change Prone Classes Using Statistical & Machine Learning Techniques

Abstract: Software today has become an inseparable part of our life. In order to achieve the ever demanding needs of customers, it has to rapidly evolve and include a number of changes. In this paper, our aim is to study the relationship of object oriented metrics with change proneness attribute of a class. Prediction models based on this study can help us in identifying change prone classes of a software. We can then focus our efforts on these change prone classes during testing to yield a better quality software. Prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…The study was conducted on the CK metrics in addition to dynamic coupling metrics. Malhotra and Jangra (2017) have studied the prediction of change-proneness of classes using object-oriented metrics. The authors conducted 10 machine learning techniques and compared the performance of the resulting models with a statistical model.…”
Section: Related Workmentioning
confidence: 99%
“…The study was conducted on the CK metrics in addition to dynamic coupling metrics. Malhotra and Jangra (2017) have studied the prediction of change-proneness of classes using object-oriented metrics. The authors conducted 10 machine learning techniques and compared the performance of the resulting models with a statistical model.…”
Section: Related Workmentioning
confidence: 99%
“…Xiao et al [344] utilized a Continuous Integration (ci) dataset and Pradel and Sen [249] generated a synthetic dataset. Apart from using the existing datasets, some other studies prepared their own datasets by utilizing various GitHub projects [4,131,209,210,296] including Apache [51,87,183], Eclipse [87,369] and Mozilla [159,206] projects, or industrial data [51]. [213].…”
Section: Data Labelingmentioning
confidence: 99%
“…Sunmin Lee and Nammee Moon proposed a location recognition system for users based on WiFi data (BSSID, RSSI) using Random Forest. In order to improve the accuracy, a radio Map was made to store BSSID efficiently and the filtered values were used as the learning data of Random Forest (Malhotra and Jangra 2017). Experiment results showed that the proposed algorithm had better accuracy, averaging 6.04% higher than the RSSI-based Random Forest location recognition.…”
Section: Related Workmentioning
confidence: 99%